The cost‐effectiveness of radial access percutaneous coronary intervention: A propensity‐score matched analysis of Victorian data. Issue 4 (22nd February 2022) - Lee, Peter; Brennan, Angela; Dinh, Diem; Stub, Dion; Lefkovits, Jeffrey; Reid, Christopher M.; Zomer, Ella; Chin, Ken; Liew, Danny
Abstract: Background: Despite evidence of the comparative benefits of transradial access percutaneous coronary intervention (PCI) over transfemoral access, its uptake remains highly varied across Australia. Few studies have explored the implications of the choice of access site during PCI from the perspective of the Australian healthcare setting. We, therefore, performed a cost‐effectiveness analysis of radial versus femoral access PCI. Methods: Data from the Victorian Cardiac Outcomes Registry (VCOR) were used to inform our economic analyses. Patients treated through either radial or femoral access PCI were propensity score‐matched using the inverse probability weighted (IPW) method, and the incidence of major bleeding and all‐cause mortality in the cohort was used to inform an economic model comprising a hypothetical sample of 1000 patients. Costs and utility data were drawn from published sources. The economic evaluation adopted the perspective of the Australian healthcare system. Results: Among a cohort of 1000 patients over 1 year, there were 19 fewer deaths, and six fewer episodes of nonfatal major bleeding in the radial group compared to the femoral group. Total cost savings attributed to radial access was AUD 1 214 688. Hence, from a health economic point of view, radial access PCI was dominant over femoral access PCI. Sensitivity analyses supported the robustness of these findings. Conclusions: Radial access is associated with improved patient outcomes and considerably lower costs relative to femoral access PCI. Our findings support radial access being the preferred approach for PCI across a variety of indications in Australia.